EFFECT OF SUPPLEMENTATION WITH DRIED DILL POWDER (ANETHUM GRANVEOLENS L.) IN DIET ON SOME BLOOD CHARACTERISTICS OF BROILED CHICKENS - Ali, H. A. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was conducted to investigate the effect of supplementation different levels of dried dill powder with diet on some physiological characteristics of broiler chickens. 336 chicks, day-old 46 gm weight /chick. Birds were randomly distributed into four treatment groups with three replicates per treatment (28 bird/replicate).Treatments were as follow:T1: control group (without any addition) T2, T3 and T4 adding dried dill powder at levels 0.4 ,0.6, 0.8% respectively. Experiment lasted five weeks, which at the end measurements of protein, glucose, albumin, uric acid, cholesterol, triglycerides, high density lipoprotein (HDL), low density lipoprotein (LDL) and very low density lipoprotein (VLDL) in blood serum were done. The results showed a significant (p<0.05) increase in protein and HDL levels in blood serum of dill treatments compared to control group. While ,albumin and triglycerides levels were not affected by supplementing the dried dill powder, whereas a significant decrease (p<0.05) in levels of serum glucose, uric acid, cholesterol, LDL and VLDL in T2, T3 and T4. It can be concluded from this study that supplementation of dried dill powder to broiler diets led to an improvement of lipoprotein blood serum characteristics.